Population Pharmacokinetics of Liposomal Irinotecan in Patients With Cancer. Issue 6 (5th June 2017) - Adiwijaya, BS; Kim, J; Lang, I; Csõszi, T; Cubillo, A; Chen, J‐S; Wong, M; Park, JO; Kim, JS; Rau, KM; Melichar, B; Gallego, JB; et al.
Abstract : Nanoliposomal irinotecan (nal‐IRI) is a liposomal formulation of irinotecan with a longer half‐life (t1/2 ), higher plasma total irinotecan (tIRI), and lower SN‐38 maximum concentration ( C max ) compared with nonliposomal irinotecan. Population pharmacokinetic (PK) analysis of nal‐IRI was performed for tIRI and total SN‐38 (tSN38) using patient samples from six studies. PK‐safety association was evaluated for neutropenia and diarrhea in 353 patients. PK‐efficacy association was evaluated from a phase III study in pancreatic cancer NAPOLI1. Efficacy was associated with longer duration of unencapsulated SN‐38 (uSN38) above a threshold and higher Cavg of tIRI, tSN38, and uSN38. Neutropenia was associated with uSN38 C max and diarrhea with tIRI C max . Baseline predictive factors were race, body surface area, and bilirubin. Analysis identified PK factors associated with efficacy, safety, and predictive baseline factors. The results support the benefit of nal‐IRI dose of 70 mg/m 2 (free‐base; equivalent to 80 mg/m 2 salt base) Q2W over 100 mg/m 2 Q3W.